2020
DOI: 10.1186/s12912-020-00497-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing recruitment and retention of male nurses in Macau and mainland China: a collaborative, qualitative study

Abstract: Background Macau and the Mainland China have different political and socio-economic policies but are both influenced by Chinese culture. By comparing the professional development experiences of male nurses from Macau and the Mainland, this study aims to explore factors influencing the recruitment and retention of male nurses. Methods A collaborative, qualitative approach was adopted in which researchers from Macau and the Mainland were jointly involved in carrying out interviews and analyzing data. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…A previous study found that men in Macau did not think a lot about leaving nursing, while male nurses on the mainland often felt uncertain about their career prospects. At present, the salary of nurses in Macao is much higher than the average income levels ( 38 ). Moreover, in most Hospitals in China, nurses with diplomas and degrees have similar responsibilities and salaries, with a difference of about $50 ( 6 ), which may influence male nursing students' professional recognition and ambition.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study found that men in Macau did not think a lot about leaving nursing, while male nurses on the mainland often felt uncertain about their career prospects. At present, the salary of nurses in Macao is much higher than the average income levels ( 38 ). Moreover, in most Hospitals in China, nurses with diplomas and degrees have similar responsibilities and salaries, with a difference of about $50 ( 6 ), which may influence male nursing students' professional recognition and ambition.…”
Section: Discussionmentioning
confidence: 93%
“…The job characteristic dimension results indicate that the male nurses' work autonomy is not high. Most male nurses in China do not like the nursing profession and feel uncertain about the future of their careers (Mao et al., 2020). A higher proportion of male than female nurses have reportedly been victims of physically aggressive behaviour (Edward et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…C.6 Male Nurses: Shame and Embarrassment Some nursing students were ashamed by their perceived rejection by society, their families, their friends, and other healthcare professionals when they expressed their desire to become nurses [48]. This rejection and the possibility or reality of being mocked [37,41] provoke shame in many male nurses, who opt to avoid telling people that they are nurses [23,31,35]; conceal their work using ambiguous terms such as 'healthcare professional' [31,41]; or hide in units where little contact with the public is required [29].…”
Section: C5 Male Nurses: a Sexual Threatmentioning
confidence: 99%
“…In Sales-Mauricio and colleagues' study [48], 10.5% of respondents stated that their desire to become nurses was met with comments from their social circles such as: "But you're clever, why don't you study medicine?". In Mao and colleagues' paper [31], the comments made were "You're a guy. Why nursing?…”
Section: C8 Male Nurses: Should Be Doctorsmentioning
confidence: 99%
See 1 more Smart Citation